Do fire-related cues, including smoke-water, karrikinolide, glyceronitrile and nitrate, stimulate the germination of 17 Anigozanthos taxa and Blancoa canescens (Haemodoraceae)? - Downes, Katherine; Light, M.; Posta, M.; Kohout, L.; van Staden, J. (CSIRO Publishing, 2014)
Many species in fire-prone environments germinate after fire including most taxa in the genus Anigozanthos Labill. Following preliminary studies with Anigozanthos manglesii D.Don subsp. manglesii, the response of several Anigozanthos taxa to germination stimulants relating to the post-fire environment including smoke, karrikinolide (KAR1, 3-methyl-2H-furo[2,3-c]pyran-2-one) and nitrate were compared in seed when freshly collected and after a period of burial. Following after-ripening, the response of seed to water, smoke-water, KAR1 and glyceronitrile (2,3- dihydroxypropanenitrile) was examined. Seed of 16 Anigozanthos taxa, and the related monotypic genus Blancoa Lindl., were highly dormant at maturity. Investigations of eight Anigozanthos taxa and B. canescens indicated that these taxa had morphophysiological dormancy. Following a period of either 3- to 4 months or 1 year of burial and exhumation in autumn, many taxa remained dormant. However, dormancy was alleviated and smoke-water stimulated some germination of A. manglesii subsp. manglesii, A. flavidus DC., A. viridis Endl. subsp. viridis, and A. viridis Endl. subsp. Cataby (S.D. Hopper 1786). Nitrate also stimulated germination of A. flavidus in the light. Following 3–3.5 years of laboratory after-ripening, 13 of the 17 Anigozanthos taxa examined were smoke-responsive. When testing individual smoke-derived compounds these taxa germinated in response to glyceronitrile and not KAR1. In contrast, smoke-responsive B. canescens seed responded to KAR1 and not glyceronitrile. These findings suggest a phylogenetic link between responsiveness to different chemicals in smoke in this family that may shed light on the evolutionary development of these smoke responses.